A Mobile Robotic System for the Inspection and Repair of SG Tubes in NPPs. (5th April 2016) - Seo, Yong-Chil; Jeong, Kyungmin; Shin, Hocheol; Choi, YoungSoo; Lee, Sung-Uk; Noh, Sunyoung; Kim, Tae Won; Cho, Jai Wan
The reliability and performance of a steam generator (SG) is one of the serious concerns in the operation of pressurized water nuclear power plants. Because of high levels of radiation, robotic systems have been used to inspect and repair SG tubes. In this paper, we present a mobile robotic system that positions the inspection and repair tools while hanging down from the tube sheets where the tubes are fixed. All of the driving mechanisms of the mobile robot are actuated by electric motors to start its works, providing that the electric power is prepared without the additional need for an on-site air services. A special tube-holding mechanism with a high holding force has been developed to prevent falling from the tube sheets, even in the case of an electric power failure. We have also developed a quick installation guide device that guides the mobile robot to desired initial positions in the tube sheet exactly and quickly, which helps to reduce the radiation exposure of human workers during the installation work. This paper also provides on-site experimental results and lessons learned.